Experimental study of the bilateral asymmetric single-rivet occluder device for transcatheter patent foramen ovale closure with reserved interatrial septal puncture area - Wei, Yiting; Su, Yanlin; Cao, Suyan; He, Ziqian; Wang, Renrong; Qin, Xian; Feng, Yuanxi; Yang, Chengjian; Jiang, Haibin (Frontiers in Cardiovascular Medicine, 2024)
Purpose To evaluate a noval bilateral asymmetric single-rivet occluder with reserved interatrial septal puncture area for treating patent foramen ovale (PFO). Materials and methods The study established a pig model of patent foramen ovale (PFO) by puncturing the oval fossa and then performing high-pressure balloon dilation. A specially designed bilateral asymmetric occluder for the reserved interatrial septal puncture area was then. used to close the PFO through catheter-based intervention. The pigs were kept for 3 months before undergoing a second catheter-based intervention, involving interatrial septal puncture using a newly developed occluder in the reserved interatrial septal puncture area. During 6 months, the experimental pigs underwent assessment using digital subtraction angiography (DSA), echocardiography, and histological evaluation. Results A patent foramen ovale (PFO) model was successfully established in 6 pigs using the puncture atrial septum high-pressure balloon dilation method. The diameter of the unclosed PFO was measured (3.56 ± 0.25 mm). Using the newly developed occluder device, all 6 pigs with unclosed PFO underwent successful catheter-based closure surgeries, with intraoperative and postoperative transesophageal echocardiography showing excellent device positioning and complete closure without residual shunting. After 3 months of implantation, the catheter-based interatrial septal puncture was performed through the reserved interatrial septal puncture area, and all procedures were successful. Immediately following euthanasia, a histological examination revealed intact and undamaged occluder devices with visible puncture holes in the reserved interatrial septal puncture area. No fracture of the nitinol wire was observed, and the surface of the occluder device showed coverage of endothelial and connective tissues. Utilizing a bilateral asymmetric single-rivet occluder device implanted through the reserved interatrial septal puncture area has proven effective in closing PFO. After implantation, the occluder device allows subsequent interatrial septal puncture procedures through the reserved area. Conclusion The novel occluder device demonstrated excellent closure performance, biocompatibility, and puncturability in the experiment. This indicates the feasibility of conducting further catheter-based interventions on the interatrial septum.